Doa dalam Perspektif al-Qur’an - Mursalim Mursalim (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2011)
Prayer is part of the remembrance. As a petition, the prayer in religion is positioned as part of a means to draw closer to God. Thus, prayer to God for those who believe more to a condition that can provide sikaf optimistic, contented heart, and a sense of calmness in the soul, thus providing an inner strength in dealing with various problems. Prayer to God for granted-at least not in the Koran, there are several requirements that must be met by a person who prays, the response to this call and full of conviction petition, only to God, an attitude ‘tawadhu’ (not too louder voice), and pray to God by using His names.